Does type 2 diabetes increase rate of cognitive decline in older Mexican Americans? - Mayeda, Elizabeth R; Haan, Mary N; Yaffe, Kristine; Kanaya, Alka M; Neuhaus, John (Alzheimer disease and associated disorders, 2015)
Estimating effects of diabetes on cognitive change among older Mexican Americans is important, yet challenging, because diabetes and cognitive decline both predict mortality, which can induce survival bias. Older Mexican Americans in the Sacramento Area Latino Study on Aging (n=1634) completed Modified Mini-Mental State Exams (3MSE) and diabetes assessments up to 7 times (from 1998 to 2007). We examined baseline and new-onset diabetes and cognitive decline with joint longitudinal-survival models to account for death. At baseline, 32.4% of participants had diabetes and 15.8% developed diabetes during the study. During the study period, 22.8% of participants died. In joint longitudinal-survival models, those with baseline diabetes experienced faster cognitive decline (P=0.003) and higher mortality (hazards ratio=1.88; 95% confidence interval, 1.48-2.38) than those without diabetes. Cognitive decline and mortality were similar for those with new-onset diabetes and those without diabetes. For a typical person, 3MSE scores declined by 2.3 points among those without diabetes and 4.3 points among those with baseline diabetes, during the last 6 years of study. Ignoring the impact of death yielded a 17.0% smaller estimate of the effect of baseline diabetes on cognitive decline. Analyses that overlook the association between cognitive decline and mortality may underestimate the effect of diabetes on cognitive aging.